The Genetic Changes of Hepatoblastoma - Chen, Huitong; Guan, Qian; Guo, Huiqin; Miao, Lei; Zhuo, Zhenjian (Frontiers in Oncology, 2021)
Hepatoblastoma is the most common malignant liver cancer in childhood. The etiology of hepatoblastoma remains obscure. Hepatoblastoma was closely related to genetic syndromes, hinting that hepatoblastoma is a genetic predisposition disease. However, no precise exposures or genetic events are reported to hepatoblastoma occurrence. During the past decade, significant advances have been made in the understanding of etiology leading to hepatoblastoma, and several important genetic events that appear to be important for the development and progression of this tumor have been identified. Advances in our understanding of the genetic changes that underlie hepatoblastoma may translate into better patient outcomes. Single nucleotide polymorphisms (SNPs) have been generally applied in the research of etiology’s exploration, disease treatment, and prognosis assessment. Here, we reviewed and discussed the molecular epidemiology especially SNPs progresses in hepatoblastoma to provide references to future studies and promote the study of hepatoblastoma’s etiology.